Discourse constructions of youth identities - Androutsopoulos, Jannis K.; Georgakopoulou, Alexandra (Pragmatics & beyond, 2003)
This volume sets out to foreground the issues of youth identity in the context of current sociolinguistic and discourse research on identity construction. Based on detailed empirical analyses, the twelve chapters offer examinations of how youth identities from late childhood up to early twenties are locally constructed in text and talk. The settings and types of social organization investigated range from private letters to graffiti, from peer group talk to video clips, from schoolyard to prison. Comparably, a wide range of languages is brought into focus, including Danish, German, Greek, Japa.